Cognitive and Emotional Stressors of Child Homicide Investigations on U.K. and Danish Police Investigators. Issue 3 (August 2018) - Roach, Jason; Sharratt, Kathryn; Cartwright, Ashley; Skou Roer, Thomas
In a previous paper, key differences in the form and manifestation of cognitive and emotional stress experienced by investigators of adult and child homicide were identified, along with a cursory look at how investigators commonly deal or cope with these effects. In this article, the findings from 11 interviews with U.K. and Danish police officers with experience of investigating both adult and child homicides suggest that child homicide investigations can have a profoundly different effect on police investigators that can vary between officers. The effects experienced and coping strategies employed were similar among officers in Denmark and the United Kingdom, and these included becoming more emotionally closed and engaging in regular sport and exercise. The findings hold important implications for police training and for the welfare of current and future police homicide investigators particularly where the victim is a child.